Механізм державного управління “зеленою” національною економікою - Бублик, М. І. (Видавництво Львівської політехніки, 2015)
Розглядаються нові напрями державного управління екологічною політикою та політикою “зеленої” економіки в Україні та світі з метою зменшення обсягів техногенних збитків у національному господарстві пропонується метод вибору цільових програм, проектів та заходів щодо зменшення техногенної шкоди, відповідно до обсягу доступного фінансування. In the article new directions of state governance of environmental policy and “green” economy are examined in Ukraine and the world, in order to reduce the volume of technogenic losses in the national economy going is offered a method for selection of targeted programs, projects or activities to reduce man-made damage in accordance with the amount of funding available. Solving these problems involves not only creating a favorable environment for greening production and implementation of the policy of “green” economy, but also the formation of new government regulation of technogenic (man-made) damages at the macro level. The problem of construction of method of choice system of state regulation of man-made damages at the macro level has particular relevance. Based on our research and the obtained results, we recommend to include the method of choice system of state regulation of man-made damage into the mechanism of their state regulation as part of the system. The proposed method with the methods of management of all resources and information flows at national level will improve the effectiveness of state regulation. The method of selecting that type of system of state regulation of production technogenic load, which will give opportunity to minimize man-made damage and set up effective measures to reduce pollution, improve health and life expectancy has been developed at the level of the national economy. Thus, the introduction of the proposed method of choice system of state regulation of man-made damage taking into account features clusters of economic activities into the mechanism of their state regulation make it possible to significantly increase the effectiveness of management decisions on the development of the national economy, modernizing the structure of its economic activity and reconstruction of industrial objects of potential manmade threat to the environment and society to improve the quality of life and improve the environment.
The mechanism of state administation of “green” national economy
Keywords: державне управління; екологічна політика; політика “зеленої” економіки; техногенні збитки; експертні методи; метод вибору; governance; environmental policy; the policy of “green” economy; man-made damage; expert methods; the method of choice